APPLICATION OF CURIOSITY TOWARD TODDLER POSITIVE THINKING ATTITUDE IN FACING THE ERA SOCIETY 5.0 - Laili, Siti Indatul; Peni, Tri; Ratnaningsih, Tri (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Era 5.0 is an era of digitalization technology that can influence the development of toddlers because the development of cognitive function, the immune system, and physical growth occur rapidly. Including toddlers' high curiosity about technology, one of which is using mobile devices. The purpose of this research was to prove the influence of applying curiosity on toddlers' positive thinking attitudes in facing the era society 5.0 in East Wonoayu Hamlet, Dukuhmojo Village, Mojoagung District, Jombang Regency. The design of this research used a one-group pra-post test design. The population in this research were all mothers and toddlers in East Wonoayu Hamlet, Dukuhmojo Village, Mojoagung District, Jombang Regency totaling 47 children. The sampling technique used was total sampling. The samples in this research were all mothers and toddlers in East Wonoayu Hamlet, Dukuhmojo Village, Mojoagung District, Jombang Regency totaling 47 children. The instrument used to assess positive thinking attitudes is a questionnaire. Data processing starts from editing, coding, scoring, and data analysis was carried out using the cross table. The research results showed that there was an increase before the implementation of curiosity as many as 47 (100%) respondents had a moderate positive thinking attitude. And after implementing curiosity 17 (36%) respondents had a high positive thinking attitude. curiosity will motivate a person to continue looking for and knowing new things so that they can increase their knowledge and experience in the learning process.